Indonesian Language Learning Based on Local Wisdom: Derivational and Inflectional Morphological Processes - Sesa, Elia; R, Mantasiah; Syamsudduha, Syamsudduha (Journal La Edusci, 2025)
This study examines the derivative and morphological inflection processes in the ritual speech of Rambu Solo in the Toraja tribe and how these are applied in learning the Indonesian language through local wisdom. By utilizing qualitative approach, the study explores the pattern of affixations e.g., pa-, si-, ma-, and ta-, and suffixes e.g., -na which are dialects of the Toraja language that express possession, agency, voice, and grammatical ties. The researcher surveyed cultural leaders, school teachers and language scholars by interviewing them and also recording the sacred speeches. The observations show that such morphological structures are not only rich in language but also rich in the cultural significance of the Toraja community because it demonstrates values to the core and social makeup. This research paper also shows how incorporation of these morphological aspect in the Indonesian language learning enhance contextual learning, increase the level of metalinguistic awareness and conducive towards ensuring the survival of indigenous languages. The study fills the core deficiency located in the sphere of language education literature, which tended to ignore including the local linguistic resources into formal studies. Teachers, cultural elders, were some of the participants who did not object to the use of traditional forms of speech as learning aids, but caution had to be taken to ensure that it is done respectfully and correctly. This incorporation is seen as corresponding to the objectives of Independent Learning curriculum because it removes rigid culturally-oriented learning environments.